Improvement of survival and development of Pacific white shrimp Litopenaeus vannamei larvae by feeding taurine enriched rotifers - Dedi Jusadi; Syarifah Ruchyani; Ing Mokoginta; Julie Ekasari (Jurnal Akuakultur Indonesia)
ABSTRACT